Prodrug-based nano-delivery strategy to improve the antitumor ability of carboplatin in vivo and in vitro. (1st January 2021) - Lang, Tingting; Li, Nuannuan; Zhang, Jing; Li, Yi; Rong, Rong; Fu, Yuanlei
Abstract: Chemotherapy plays a major role in the treatment of cancer, but it still has great limitations in anti-tumor effect. Carboplatin (CAR) is the first-line drug in the treatment of non-small cell lung cancer, but the therapeutic effect is demonstrated weak. Therefore, we modified CAR with hexadecyl chain and polyethylene glycol, so as to realize its liposolubility and PEGylation. The synthesized amphiphilic CAR prodrugs could self-assemble into polymer micelles in water with an average particle size about 11.8 nm and low critical micelles concentration (0.0538 mg·mL –1 ). In vivo pharmacodynamics and cytotoxicity experiment evidenced that the polymer micelles were equipped with preferable anti-tumor effect, finally attained the aim of elevating anti-tumor effect and prolonging retention time in vivo . The self-assembled micelles skillfully solve the shortcomings of weak efficacy of CAR, which provides a powerful platform for the application of chemical drug in oncology.